2011
DOI: 10.3201/eid1703.100502
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusInfections in US Veterans, Maryland, USA, 1999–20081

Abstract: Trends in Staphylococcus aureus infections are not well described. To calculate incidence in overall S. aureus infection and invasive and noninvasive infections according to methicillin susceptibility and location, we conducted a 10-year population-based retrospective cohort study (1999–2008) using patient-level data in the Veterans Affairs Maryland Health Care System. We found 3,674 S. aureus infections: 2,816 (77%) were noninvasive; 2,256 (61%) were methicillin-resistant S. aureus (MRSA); 2,517 (69%) were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
26
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 24 publications
3
26
1
1
Order By: Relevance
“…Recently, this clone has also been implicated as a cause of health care-associated (HA-MRSA) and invasive infections (22,39,45). However, recent studies have demonstrated an overall increase of noninvasive, community-onset, MRSA infections, while the incidence of HA-MRSA and invasive infections declined (8,21,31,51). Similar changes in the MRSA epidemiology among European hospitals have been reported in numerous studies as well (6,9,14,16).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Recently, this clone has also been implicated as a cause of health care-associated (HA-MRSA) and invasive infections (22,39,45). However, recent studies have demonstrated an overall increase of noninvasive, community-onset, MRSA infections, while the incidence of HA-MRSA and invasive infections declined (8,21,31,51). Similar changes in the MRSA epidemiology among European hospitals have been reported in numerous studies as well (6,9,14,16).…”
supporting
confidence: 64%
“…This species ranks as the main pathogen responsible for nosocomial bloodstream infections (BSI), hospital-acquired bacterial pneumonia (HABP) and ventilator-acquired bacterial pneumonia (VABP), and skin and skin structure infections (SSSI) (20,25). Many infections are caused by methicillin-resistant S. aureus (MRSA) isolates, and recent studies have demonstrated an increased MRSA incidence over the last decade (31,34,43,51). These facts, along with complicating risk factors, comorbidity, and mortality (between 40 and 60%), result in extended hospitalizations, escalated health care costs, and the requirement of potent, broad-spectrum agents often used in combination regimens (7).…”
mentioning
confidence: 99%
“…The risk of invasive S. aureus infections is significantly higher among certain subgroups, including hemodialysisdependent patients and postoperative patients (12)(13)(14).These high-risk subpopulations are potential candidates for novel forms of prevention or treatment against invasive S. aureus infections.…”
mentioning
confidence: 99%
“…Skin and soft tissue infections (SSTI) were the most commonly reported type of infection (1), and 65% of SSTI were caused by MRSA, as reported by one VA hospital (2). As a result, in 2007, the VA system instituted a nationwide acute-care surveillance program in their 153 medical centers with the aim of decreasing both carriage and disease due to MRSA (3).…”
mentioning
confidence: 99%